Efektifitas Penggunaan Buku Kia dengan Video Terhadap Pengetahuan Persiapan dan Tanda Awal Persalinan Pada Primigravida di TPMB Sri Nugrahaningsih - Kasih Misrini; Nur Ismi Wahyuni (Malahayati Nursing Journal, 2024)
ABSTRACT Knowledge of pregnant women about the signs of labor is very important, because by knowing the signs of labor it can be known that labor is close and ready for labor so that mothers and families can go to the hospital or maternity clinic fasterPreparation for childbirth is something that must be done by every pregnant woman to face the birth of a baby, especially at the age of terimester III where the phase of waiting for the birth of the baby, the preparation needed includes material, physical and mental (psychology). Extension organizers need to use media so that the message they want to convey is conveyed to the counseling participants. Media is divided into three, namely audio, visual, and audio visual. Purpose: to determine the effectiveness of KIA books with videos on increasing knowledge about childbirth preparation and early signs of marriage in primigravida mothers in TPMB. Research Method: This study is experimental with quasy experimental control group pre test and post test design with quantitative approach. In this study, the population was all Third Trimester Pregnant Women who came to visit TPMB Sri Nugrahaningsih totaling 40 people. The study was divided into 2 groups. Research Results: Based on the statistical test of the Paired Sample t-test with SPSS software and produced a p-value of 0.024 0.05 which means that there is a significant difference between the mother's knowledge before being given KIA book counseling and the mother's knowledge after being given KIA book counseling. Test Results Paired Sample t-test with SPSS software and produced a p-value of 0.011 0.05 which means that there is a significant difference between the mother's knowledge before being given video counseling and the mother's knowledge after being given video counseling. Conclusion: the video is more effective than the KIA book in increasing knowledge about childbirth preparation and early signs of marriage in primigravida mothers at TPMB Sri Nugrahaningsih. Keywords: Health Promotion, Husband Support, Perception, Decision Making, Iva Test  ABSTRAK Persiapan persalinan merupakan suatu hal yang harus dilakukan oleh setiap ibu hamil untuk menghadapi kelahiran buah hati terlebih pada usia terimester III dimana fase menunggu kelahiran sang buah hati, persiapan yang diperlukan meliputi materi, fisik dan mental (psikologi). Penyelenggara penyuluhan perlu menggunakan media agar pesan yang ingin di sampaikan menjadi tersampaikan ke peserta penyuluhan. Media dibagi menjadi tiga yaitu audio, visual, dan audio visual. Tujuan penelitian ini untuk mengetahui Efektivitas Buku KIA dengan video terhadap peningkatan pengetahuan tentang persiapan melahirkan dan tanda awal persalianan pada ibu primigravida di TPMB. Penelitian ini bersifat eksperimen dengan desain quasy eksperimental control group pre test dan post testdengan pendekatan kuantitatif. Pada penelitian ini yang dijadikan populasi adalah seluruh Ibu Hamil Trimester III yang datang berkunjung ke TPMB Sri Nugrahaningsih yang berjumlah 40 orang. pada penelitian terbagi menjadi 2 kelompok. Berdasarkan uji statistik Uji Paired Sample t-test dengan software SPSS dan menghasilkan p-value sebesar 0.024 0,05 yang berarti yang menunjukkan bahwa ada perbedaan yang bermakna antara pengetahuan ibu sebelum diberikan konseling buku KIA dengan pengetahuan ibu sesudah diberikan konseling buku KIA.  Hasil Uji Paired Sample t-test dengan software SPSS dan menghasilkan p-value sebesar 0.011 0,05 yang berarti yang menunjukkan bahwa ada perbedaan yang bermakna antara pengetahuan ibu sebelum diberikan konseling video dengan pengetahuan ibu sesudah diberikan konseling vide.  Sehingga dapat disimpulkan bahwa video lebih efektf dibandingkan dengan buku KIA dalam peningkatan pengetahuan tentang persiapan melahirkan dan tanda awal persalianan pada ibu primigravida di TPMB Sri Nugrahaningsih. Kata Kunci: Buku KIA, Video Pembelajarn, Tanda Peersalinan, Kehamilan